2016
DOI: 10.1177/0092055x16654744
|View full text |Cite
|
Sign up to set email alerts
|

Sociology Faculty Members Employed Part-time in Community Colleges

Abstract: Among all faculty members teaching in colleges and universities in the United States today, the proportion employed part-time has been increasing steadily and represents the fastest growing segment of the postsecondary faculty (Anderson 2002; Coalition on the Academic Workforce 2012). In 1975-1976, 31 percent of all faculty members were employed part-time; by 2011, they represented 51 percent (Curtis 2014). Looking within the parttime faculty, the distribution across institution types is far from even. In 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Dalam penyampaian materi, masih berpusat pada guru dan siswa kurang aktif. Apabila suasana belajar tersebut dibiarkan, maka akan berakibat pada kejenuhan dan kebosanan belajar di kelas dan akan berdampak pada hasil belajar siswa tidak mencapai KKM (Curtis, Mahabir, & Vitullo, 2016). Melihat kenyataan diatas, maka perlu perbaikan proses belajar di kelas dengan menerapkan metode-metode pembelajaran yang melibatkan siswa secara aktif (Royani, 2015).…”
Section: Pendahuluanunclassified
“…Dalam penyampaian materi, masih berpusat pada guru dan siswa kurang aktif. Apabila suasana belajar tersebut dibiarkan, maka akan berakibat pada kejenuhan dan kebosanan belajar di kelas dan akan berdampak pada hasil belajar siswa tidak mencapai KKM (Curtis, Mahabir, & Vitullo, 2016). Melihat kenyataan diatas, maka perlu perbaikan proses belajar di kelas dengan menerapkan metode-metode pembelajaran yang melibatkan siswa secara aktif (Royani, 2015).…”
Section: Pendahuluanunclassified
“…The experiences of several participants agreed with this literature, indicating that because their students were focused on either transferring to four-year colleges or seeking employment directly after receiving an associate degree, the need for faculty to have information on the policies and logistics surrounding such goals was critical for student success. Supporting the finding of Curtis et al (2016), three of the part-time participants in the study felt that not being provided with updated information had left them at one time or another feeling unsupported or unappreciated as critical members of the campus community. This underscores Smith's (2015) finding that the part-time, non-tenure track adjunct instructors that colleges and universities are hiring at increasing rates frequently lack resources, development and training.…”
Section: Students Success Is Dependent On Faculty Knowledge Of Campusmentioning
confidence: 63%
“…The perceptions faculty have of one another's roles as educators (and subsequent quality of teaching), be they full or part-time, can influence future best practices for creating a single faculty body. Through a study of part-time, community college sociology faculty, Curtis, Mahabir, & Vitullo (2016) concluded that administrators and full-time faculty needed to provide support and introduction to their adjunct colleagues in order to increase student success. This study and others like it, while beneficial to understanding the need for adjunct faculty inclusion, continue to promote the separation of full-time and part-time faculty.…”
Section: Summationmentioning
confidence: 99%
See 2 more Smart Citations